(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
. A device is known that includes a looper rigidly mounted on an oscillating shaft and a stationary spreader that holds a loop of needle thread at certain moments of the loop formation process. The necessary rotational or oscillatory movement of the looper performed along the stitch line predetermines the presence of a looper shaft located in bearings across the stitch line and having elements of kinematic connection with the transmission link, in the form of a gear or rocker arm with a rotational kinematic pair. As a result, when using known methods of forming a single-thread chain stitch (the output link of the corresponding mechanisms, including a looper, a shaft located across the stitch line, with elements of kinematic connection with the transmission link and the stand), relatively large cross-sectional dimensions of the cavity of the hose platform in which the specified output link. This drawback of existing methods and corresponding mechanisms does not allow their use in cases where the cross-sectional dimensions of the hose platform, determined by the technological characteristics of the product being processed, for example, the diameter of the product having a cylindrical shape, should be smaller than those dimensions that can be obtained using known methods and mechanisms.